Algebra for college students - Richard N. Aufmann (Houghton Mifflin, 2008)
Algebra for College Students is a mathematically sound treatment of topics intended for students who have successfully completed a first-year algebra course. College algebra level topics are integrated at appropriate places with those covered in Aufmann's Intermediate Algebra with Applications, 7/e (c2008). This content includes Graphs of Polynomial Functions, Zeros of Polynomial Functions, Graphs of Rational Functions, and Introduction of Probability and Introduction to Statistics. The hallmarks of the Aufmann developmental texts that have made them market leaders are an interactive approach in an objective-based framework, a clear writing style, and an emphasis on problem solving strategies, offering guided learning for both lecture and self-paced courses